2022
DOI: 10.52547/johe.11.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Noise Exposure and Mental Health Components among Iranian Steel Workers, 2021

Abstract: Background: Noise is an important occupational safety and health issue in many workplaces. Noise annoyance is a strong measurable mental response. It is a reaction that a person expresses to the noise exposure. Thus, this study investigates the correlation between noise exposure and its annoyance in terms of mental health components. Materials and Methods: This was a correlational descriptive study conducted on 100 workers. Respondents were recruited by a simple random sampling method. The equivalent sound lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…In a study conducted in one of the mines, a significant relationship was observed between the level of noise exposure and the communication skills of workers (15), which does not match the results of the present study. Job stress is one of the factors that occurs as a result of noise exposure in the workplace and can affect communication skills (38).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in one of the mines, a significant relationship was observed between the level of noise exposure and the communication skills of workers (15), which does not match the results of the present study. Job stress is one of the factors that occurs as a result of noise exposure in the workplace and can affect communication skills (38).…”
Section: Discussioncontrasting
confidence: 99%
“…Communication is one of the most important factors in improving productivity and job satisfaction. Previous evidence suggests that poor communication between people in the workplace can increase errors (15). In addition, as previously mentioned, noise can cause mental disorders and depression.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also people with cardiovascular diseases, diabetes, congenital hearing impairment and any use of antidepressant drugs were excluded from the study [14], at the conclusion of the study, 50 workers were chosen for the exposed group and 50 workers were chosen for the control group (refer to Eq. ( 1)) [21,22]. The participants were included in the study after giving their informed consent.…”
Section: Participantsmentioning
confidence: 99%
“…In general, the adverse effects of sound can be divided into three categories: psychological effects, interference with activities and physiological effects [1,3]. Factors such as the level of sound exposure, the duration of exposure and the frequency spectrum determine the extent and nature of sound effects.…”
Section: Application Of Genetic Algorithm In Acousticsmentioning
confidence: 99%